DESIGN OF BALANCED SCORE CARD IN A NEWSPAPER COMPANY - Giri Pratama Ilyas; Iman Harymawan (Berkala Akuntansi dan Keuangan Indonesia, 2018)
The purpose of this study is to show the design of the Balanced Scorecard at the largest daily newspaper company in eastern Indonesia and to explain the causal relationship between strategic objectives on the Strategy Map to achieve the company's vision and mission. This research uses a case study qualitative approach. The data were obtained by semi-structured interviews from several informants related to the preparation of strategic objectives in daily newspaper companies. The formulation of strategic targets and Key Performance Indicators (KPI) were identified through the description of PT.XYZ's vision and mission. After that, the identified strategic objectives and KPIs are defined into the Balanced Scorecard. The author uses the daily newspaper company XYZ because PT. XYZ does not have a framework that links between strategic objectives and KPIs that are in accordance with the vision and mission of PT. XYZ. The results of this study indicate that the design of the balanced scorecard at PT.XYZ produces 14 strategic objectives and 26 KPIs. The growth and learning perspective has 3 strategic objectives and 7 KPIs. The internal business process perspective has 6 strategic objectives and 11 KPIs. The customer perspective has 2 strategic goals and 4 KPIs. The financial perspective has 3 strategic objectives and 4 KPIs. The setting of strategic targets and KPIs from the perspective of the Balanced Scorecard is in line with the company's vision and mission. The causal relationship flow from the strategic objectives to the company's vision and mission is contained in the Strategy Map.